Contralateral adrenal width predicts the duration of prolonged post‐surgical steroid replacement for subclinical Cushing syndrome. (12th April 2018) - Sugiura, Masahiro; Imamura, Yusuke; Kawamura, Koji; Yamamoto, Satoshi; Sazuka, Tomokazu; Nakamura, Kazuyoshi; Sakamoto, Shinichi; Nagano, Hidekazu; Koide, Hisashi; Tanaka, Tomoaki; Imamoto, Takashi; Komiya, Akira; et al.
Abstract : Objectives: To identify pre‐treatment factors affecting the duration of post‐surgical steroid replacement in patients undergoing adrenalectomy for subclinical Cushing syndrome. Methods: The present retrospective analysis included 64 patients who underwent unilateral laparoscopic adrenalectomy for subclinical Cushing syndrome. Adrenal tumor and contralateral adrenal sizes together with various clinical factors were studied in association with the duration of post‐surgical steroid replacement. Adrenal tumor and contralateral adrenal size were measured at the level of the maximum transverse plane of the adrenal glands using computed tomography scan or magnetic resonance imaging. Cox's proportional hazards model was used for the statistical analysis. Results: All 64 patients were treated with post‐surgical steroid replacement after adrenalectomy. The median duration of the steroid treatment was 6 months. When assessing the duration of post‐surgical steroid replacement, contralateral adrenal volume <0.745 cm 3, contralateral adrenal width <6.15 mm and serum cortisol after a 1‐mg dexamethasone suppression test >2.65 μg/dL were significant predictors of prolonged post‐surgical steroid treatment on univariate analysis. On multivariate analysis, contralateral adrenal width <6.15 mm was the only independent predictive factor for the prolonged post‐surgical steroid replacement. Conclusions: Contralateral adrenal width seems to represent a significant predictive factor for the duration of post‐surgical steroid replacement in subclinical Cushing syndrome patients. Pre‐surgical assessment of image findings might help clinicians determine the total duration of steroid therapy after adrenalectomy.